2009
DOI: 10.1093/isle/isp010
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing in a Space of Ambivalent Openness: Ecocriticism and Ecophobia

Abstract: What has popularized and expanded the hermeneutic range of ecocriticism has in some ways also made ecocriticism seem immune to the challenges presented by so much of poststructuralism. Propelled and positioned within a context of environments increasingly degraded and dangerous, direct effects of our and our ancestors' behaviors, ecocriticism-seeking and espousing an immediacy and directness; an aesthetics of contact; and a firm disavowal of obscurantism, dizzying spinnings off, and general ineffectivenesshas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(18 citation statements)
references
References 3 publications
0
13
0
5
Order By: Relevance
“…Lorde, 1984). The toxic environments of climate change and homophobia are linked in the reason/erotic dualism of the Master Model (Plumwood, 1993), and cohere with other linked dualisms of white/non-white, wealthy/poor, intellectual/reproductive, a linkage that has been called erotophobia (Gaard, 2004(Gaard, (1997) and ecophobia (Estok, 2009).…”
Section: What Do We Want? a More Inclusive Climate Justicementioning
confidence: 98%
“…Lorde, 1984). The toxic environments of climate change and homophobia are linked in the reason/erotic dualism of the Master Model (Plumwood, 1993), and cohere with other linked dualisms of white/non-white, wealthy/poor, intellectual/reproductive, a linkage that has been called erotophobia (Gaard, 2004(Gaard, (1997) and ecophobia (Estok, 2009).…”
Section: What Do We Want? a More Inclusive Climate Justicementioning
confidence: 98%
“…It has even been suggested that:
mainstream ecocritics (many of the men and certainly some of the women) react strongly against ecofeminism simply because it is done mainly by women ... most men see ecofeminism as at best peripheral and at worst as a threat (which really means most men see women as peripheral or as a threat). Perhaps I am wrong, but raw sexism in its most basic form, if you ask me, is the first thing behind the backlash (Estok, , quoted in Gaard, , p. 43).
…”
Section: Ecofeminist Contributions — Reactionary or Catalytic?mentioning
confidence: 99%
“…Armbruster 1998;Chang 2009;Donovan 1991Donovan , 2009Gaard 2000Gaard , 2001Gaard , 2013. But Simon Estok's (2009) essay in the flagship journal of the Association for the Study of Literature and the Environment (ASLE) finally threw down the gauntlet. Defining 'ecophobia' as an "irrational and groundless hatred of the natural world," Estok argued that "ecophobia is rooted in and dependent on anthropocentric arrogance and speciesism"; thus, it is "difficult to take seriously... the ecocritic who theorizes brilliantly on a stomach full of roast beef on rye " (2009, 208, 216-17).…”
Section: Greta Gaardmentioning
confidence: 99%